Amplitude Stabilization of Frequency-Tunable Biquad Digital Oscillator Using Zero-Input Response Analysis - Chivapreecha, Sorawat; Suwannawach, Piyapan; Sato, Tomoaki (My University, 2025)
This paper presents an analysis of the biquad digital oscillator, which leads to design improvements in the online oscillating frequency adjustment capabilities. The requirements for signal generation in a digital oscillator without input comprise the initial conditions as well as the coefficients, which are constants. The coefficient of biquad oscillator can be modified to be a tuning parameter for changing the oscillating frequency by the users. Although the frequency of the oscillating signal can be changed as desired, however, while the system is operating, the inconsistency of the changed coefficient with the initial conditions that emerge from the retained prior states causes the signal amplitude to lose its stability. The zero-input response of a system could be theoretically examined to identify and understand this behavior. Moreover, the issue of amplitude stabilization can be looked into and resolved with the use of the zero-input response analysis develop to an improvement, which results in maintaining the amplitude of the oscillating signal after the frequency change.
Keywords: amplitude stabilization; biquad oscillator; Digital oscillator; recursive oscillator; sinewave generator; tunable frequency; zero-input response